Development of a Moodle-Based WordPress-Based Chemistry Learning Website to Improve Students' Learning Outcomes on The Elements Periodic System Material - Nur Huda; Kusumawati Dwiningsih (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Some studies say the periodic system of elements is one of the most challenging chemistry to learn, so it needs the suitable learning media. This study aims to determine the feasibility, practicality, and effectiveness of a chemistry learning website based on WordPress Moodle to improve student learning outcomes on the material of the periodic system of elements. The method used in this research is Research and Development (RD) with a 4D development model, namely Define, Design, Develop and Disseminate, tested on class X MIPA MA Amanatul Ummah Surabaya. The results of the expert validation assessment obtained data if the average percentage of content and construct conformity was 89.59% and 86.67%, respectively, in the very valid category. Furthermore, this learning media obtained a practicality percentage of 94% in the practicality test with a very practical category. In terms of media effectiveness, based on the increase in the pretest-posttest results obtained a percentage of 100% with an average n-gain score of 0.708 in the high category. Based on these results, the chemistry learning website generated from this study is valid and feasible to be used as a learning medium to improve student learning outcomes on the material of the periodic system of elements.Keywords: Learning website, WordPress, Moodle, learning outcomes.DOI:10.23960/jppk.v10.i3.2021.08